2023
DOI: 10.15252/embj.2022111719
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TDP‐43 oligomerization or RNA binding elicits distinct aggregation patterns

Abstract: Aggregation of the RNA-binding protein TAR DNA-binding protein 43 (TDP-43) is the key neuropathological feature of neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). In physiological conditions, TDP-43 is predominantly nuclear, forms oligomers, and is contained in biomolecular condensates assembled by liquid-liquid phase separation (LLPS). In disease, TDP-43 forms cytoplasmic or intranuclear inclusions. How TDP-43 transitions from physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 102 publications
2
10
0
Order By: Relevance
“…Despite extensive research on the role of TDP-43 RRMs in pathological aggregation [3,9,13,14,25,34,35,42,44,45,62], achieving a comprehensive characterization of their structural dynamics in the presence and absence of nucleic acids based on available experimental approaches, has remained difficult. To address this gap, we employed an in-silico approach that utilized multi-replica, all-atom MD simulations, initiated from configurations taken from the NMR ensemble.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite extensive research on the role of TDP-43 RRMs in pathological aggregation [3,9,13,14,25,34,35,42,44,45,62], achieving a comprehensive characterization of their structural dynamics in the presence and absence of nucleic acids based on available experimental approaches, has remained difficult. To address this gap, we employed an in-silico approach that utilized multi-replica, all-atom MD simulations, initiated from configurations taken from the NMR ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…The N and C terminal domains of TDP-43 contribute towards the formation of the biomolecular condensates through liquid-liquid phase separation (LLPS) [16][17][18][19][20][21][22][23][24]. Recently, it was demonstrated that RNA-binding maintains the NTD oligomerization crucial for NTD-driven LLPS in the nucleus [25]. Factors such as disease-associated mutations, temperature fluctuations, and exposure to oxidative, osmotic, and chemical stressors [26,27], can impair nucleic acid binding, disrupt functional LLPS and ultimately cause mislocalization to the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting this into Eq. (10) reveals that the concentration of TDP-43 aggregates can be approximated with the following equation:…”
Section: Symbolmentioning
confidence: 99%
“…ALS is distinguished by the gradual decline of motor neurons, resulting in skeletal muscle weakness and, ultimately, fatality within a span of 3 to 5 years [5,6]. TDP-43, a nuclear, intrinsically disordered, soluble protein [7,8] with a molecular weight of 43 kDa [9], is synthesized in the cytoplasm, and in healthy neurons, it predominantly resides in the nucleus [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation